If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x + 12y = -18 Solving -18x + 12y = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. -18x + 12y + -12y = -18 + -12y Combine like terms: 12y + -12y = 0 -18x + 0 = -18 + -12y -18x = -18 + -12y Divide each side by '-18'. x = 1 + 0.6666666667y Simplifying x = 1 + 0.6666666667y
| 5x-6(4x-1)=8 | | 16=24-4t | | 4+x=-4+-1x | | 3(4d+1)-9d=6(-2m+5)-4 | | x-(2x+3)=-4 | | 2x^3+7x^2-7x-30=0 | | 2w+2(6w-6)= | | 5+3x=5x+7 | | 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n |